IMPLEMENTASI MODEL PEMBELAJARAN INDEX CARD MATCHDALAM MENINGKATKAN HASIL BELAJAR MATA PELAJARANPENDIDIKAN AGAMA ISLAM PESERTA DIDIK KELASVIII A SMP NEGERI 1 KOLAKA - ERNA; M Zakariah; Andi Nurul Aulia (Universitas Sains Islam Al Mawaddah Warrahmah Kolaka, 2025)
Lack of attention of students during learning so that there are still students whose learning outcomes have not reached the criteria for achieving learning objectives. Therefore, it is necessary for teachers to find the best solutions to existing problems so that students are able to have problem solving abilities in learning that are more critical, independent and enjoyable. . So the solution to overcome existing problems is to change the teacher's learning model by implementing a new learning model in a research entitled